Mechanisms of the Flying Chain Fountain - Flekkøy, Eirik G.; Moura, Marcel; Måløy, Knut J. (Frontiers in Physics, 2018)
When a chain is released by one end from a container, it forms a striking arch extending well above the container. This phenomenon is caused by the famous Mould effect and is explained by an anomalous supply of momentum from the container, causing an upwards kick. Using simulations, experiments as well as theoretical arguments we explore the underlying mechanism for this momentum transfer and find that it depends subtly on the nature of the chain as well as on the container. Generally, it does not suffice to assume a model of the chain as a sequence of rigid elements that, due to angular moment conservation, kicks off from the container. Rather the structure of the underlying system must be included, and we analyze how this structure along with the chain mechanics may cause the required upwards force.